The Ecological Responsive Buildings: Traditional House in the Kapuas Riverside of West Kalimantan - Zain, Zairin (Komunitas, 2016)
Natural and environmental conditions were the main factor that caused people make adjustments to their residences. People need houses with the reasons are usually to meet the needs of privacy, comfort, storage of possessions, acquisition, storage and preparation of food, shelter from the weather protection from insects and/or pests, safety, kinship and social, gathering and travel, and movement. The condition of balance is achieved by the design adjustments made so that the buildings cause the least amount of impact on the surrounding environment. The advantages of the stage house for a hot and humid climate area of West Kalimantan is done to responds the ecological advantages of surrounding environment. The raised floor feature has been the best mitigation feature not only to keep dry from constant flood but also to built into the nature whilst living near riverside area. The stage house with modern concept can be designed to allow for cross ventilation, natural lighting, thermal comfort, privacy (visual and social), functionality and the effective cost for house handling.